2007
DOI: 10.1016/j.numecd.2006.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and risk of coronary heart disease: A meta-analysis

Abstract: Despite a significant association between high consumption of coffee and CHD reported among case-control studies, no significant association between daily coffee consumption and CHD emerged from long-term follow-up prospective cohort studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 76 publications
(62 reference statements)
4
74
0
16
Order By: Relevance
“…The effect does not appear to be specific to light, moderate or heavy coffee drinking. This result is consistent with current meta analyses on the coffee consumption and risk of CHD, which indicate that habitual moderate coffee drinking is associated with a lower risk of CHD in women [7], but has no effect on men [6]. These findings suggest that coffee drinking may be one of the healthy lifestyles, especially for women, which could reduce the risk of stroke and CHD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The effect does not appear to be specific to light, moderate or heavy coffee drinking. This result is consistent with current meta analyses on the coffee consumption and risk of CHD, which indicate that habitual moderate coffee drinking is associated with a lower risk of CHD in women [7], but has no effect on men [6]. These findings suggest that coffee drinking may be one of the healthy lifestyles, especially for women, which could reduce the risk of stroke and CHD.…”
Section: Discussionsupporting
confidence: 91%
“…It indicates that coffee consumption could decrease the risk of Type 2 diabetes [5]. Meta analysis on coffee consumption and coronary heart disease (CHD) shows that coffee can reduce CHD risk in women, but may have no effect in men [6,7]. There are only a few researches about the correlation between coffee consumption and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] In addition, a recent study found that coffee consumption was inversely related to markers of inflammation and endothelial dysfunction in women with type 2 diabetes. 6 Whereas the relation between coffee consumption and risk of coronary heart disease has been studied extensively, 7 few studies have examined the association of coffee drinking with stroke risk and the studies that do exist were based on a small number of cases. 8 -10 Only one study examined whether the association between coffee consumption and stroke risk differed between stroke subtypes.…”
mentioning
confidence: 99%
“…15,43 . Cafestol e Kahweol são os diterpenos que têm despertado maior interesse devido à sua atividade hiperlipemiante [35][36][37][38][39][40][41][42][43] . O teor de cafestol e kahweol na bebida varia em função do modo de preparo, ou seja, da técnica culinária de preparação da bebida.…”
Section: Café E Hipertensão Arterialunclassified
“…No Quadro 4 estão selecionados alguns estudos clínicos e epidemiológicos desta década, realizados em humanos, cujo objetivo foi investigar a associação entre ingestão de café e dislipidemia, DAC e IAM 4,19,[35][36][37][38][39][40][41][42] . Os estudos convergem para um número de cinco ou mais xícaras de 150mL/dia 1,34-37 como aquele que categoriza o indivíduo como grande bebedor de café.…”
Section: Café E Dislipidemiasunclassified